Preconception Maternal Bereavement and Infant and Childhood Mortality: A Danish Population-Based Study. Issue 8 (October 2015) - Class, Quetzal A.; Mortensen, Preben B.; Henriksen, Tine B.; Dalman, Christina; D'Onofrio, Brian M.; Khashan, Ali S.
ABSTRACT: Objectives: Preconception maternal bereavement may be associated with an increased risk for infant mortality, although these previously reported findings have not been replicated. We sought to examine if the association could be replicated and explore if risk extended into childhood. Methods: Using a Danish population-based sample of offspring born 1979 to 2009 ( N = 1, 865, 454), we analyzed neonatal (0–28 days), postneonatal infant (29–364 days), and early childhood (1–5 years) mortality after maternal bereavement in the preconception (6-0 months before pregnancy) and prenatal (between conception and birth) periods. Maternal bereavement was defined as death of a first-degree relative of the mother. Analyses were conducted using logistic and log-linear Poisson regressions that were adjusted for offspring, mother, and father sociodemographic and health factors. Results: We identified 6541 (0.004%) neonates, 3538 (0.002%) postneonates, and 2132 (0.001%) children between the ages of 1 and 5 years who died. After adjusting for covariates, bereavement during the preconception period was associated with increased odds of neonatal (adjusted odds ratio = 1.87, 95% confidence interval = 1.53–2.30) and postneonatal infant mortality (adjusted odds ratio = 1.52, 95% confidence interval = 1.15–2.02). Associations were timing specific (6 months before pregnancy only) and consistent across sensitivity analyses. Bereavement during the prenatal period was not consistently associated with increased risk of offspring mortality; however, this may reflect relatively low statistical power. Conclusions: Results support and extend previous findings linking bereavement during the preconception period with increased odds of early offspring mortality. The period immediately before pregnancy may be a sensitive period with potential etiological implications and ramifications for offspring mortality.